Standardization of civil status registration processes in the European Union, improving the exchange of civil status information between Member States (Discourse of Law and Administration, 2025)
This article discusses the lack of uniform rules for civil status registration across EU member states and the inefficient exchange of data between them, which hinders the implementation of the concept of free movement of citizens. Currently, 27 different legal, organizational, and IT systems operate, resulting in bureaucratic barriers, translation requirements, and the transfer of the obligation to inform the administration onto citizens.The author critically assesses existing EU solutions, including Regulation 2016/1191, pointing to their ineffectiveness and excessive complexity. He proposes a new model – an „EU civil status registration system” – based on standardized procedures, uniform electronic document templates, integration of Member States’ IT systems, automatic data exchange through a central European hub, and linkage to the European Digital Identity Wallet.This solution aims to eliminate bureaucratic barriers, reduce costs, increase data security and quality, enable document retrieval anywhere in the EU, and reduce paper consumption. Application examples demonstrate that information on births, marriages, and deaths could be automatically transferred between countries without involving citizens. Implementation would require the approval of all 27 countries, but—according to the author—it would bring significant social, economic, and administrative benefits.
Keywords: procesy rejestracji stanu cywilnego; cyfryzacja administracji